Women’s Pathways: Replication and Generalizability Across State Prison Systems - Brennan, Tim (Criminal justice and behavior, 2022)
This study demonstrates the replication and validation of a prior model of women’s pathways to prison that was initially developed in California Women’s prisons and subsequently implemented in the Massachusetts Department of Correction (MADOC) women’s prison in 2013. The following four main pathways were identified: (1) Quasi-normal, least disturbed, drug and situational offending; (2) lifelong abused and depressed drug abusing women; (3) socialized subcultural women, with chronic crimes and drug abuse; and (4) abused and aggressive, early onset and multi-need women with severe drugs, crime, and mental health issues. Since 2013, this model has routinely functioned in MADOC women’s prison as an internal classification (IC) for women detainees. Using a newly extracted sample of approximately 1,800 cases from MADOC, several forms of replication and validation were conducted; these demonstrated cross-sample stability, cross-method stability, and stability across time and region. Implications for theory, treatment planning, and implementation are discussed.